Hubungan Pola Asuh Orang Tua Terhadap Perilaku Sosial Anak Usia Dini - Eva Khairunisa; Mutiara Tsani; Sintya Nur Fitri; Fidrayani Fidrayani (Institut Nalanda, 2024)
This research aims to compare several aspects of research results between 2019 and 2024. The method used is Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Social behavior is closely related to children's behavior in adapting to the rules of society in the surrounding environment. A person's social behavior can be seen from the reciprocal relationships between each individual through the positive response patterns of each party. To determine someone who has a social spirit, their behavior must reflect the achievement of the socialization process between relationships, meanwhile individual personnel who have a non-social personality will be seen from their behavior as not achieving the socialization process within their social circle. Our research problem is how much influence parents' parenting styles have on the development of children's social behavior, so that positive interactions are needed for children, such as emotional support and effective communication. This research aims to determine the influence of parenting patterns on the social behavior of early childhood. In this research, the results of the discussion can be seen through the effect size of 6 previous studies. The results of the research show that there is a significant relationship between parenting styles and the social behavior of early childhood. The facts show that parenting style has the highest result, namely 4.378, and parental involvement in the field of social behavior education has a medium result, namely 0.507